Effects of Labor Values on Subjective Well-Being: The Mediating Role of Altruistic Tendencies - Chao, Xiaomei; Gu, Yuliang (Frontiers in Psychology, 2021)
This study examined the mediating role of altruistic tendency in the association between labor value and subjective well-being. 2691 Chinese students (1504 males, 1187 females) completed the Labor Values Scale，the Positive Affect and Negative Affect Scale，the Satisfaction with Life Scale and Altruistic Tendency Scale. Results demonstrated that Labor values were associated positively with life satisfaction and positive affect, while negatively with negative affect. Altruistic tendency was positively correlated with Labor values, subjective well-being and positive affect, while negatively with negative affect. Furthermore, Altruistic tendency served as a mediator linking labor values and positive/negative affect. These results confirmed the relationship between labor values and subjective well-being, and revealed the mechanism of altruism tendency between the two. This study represents a theoretical explanation and empirical evidence for understanding the conditions and mechanisms of subjective well-being.